2016
DOI: 10.1007/s12288-016-0685-8
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Mean Platelet Volume (MPV) and JAK-2 Mutation on Thrombosis in Chronic Myeloproliferative Diseases

Abstract: Thrombosis and bleeding are the main complications of chronic myeloproliferative diseases. Mean platelet volume (MPV) is an important indicator of the platelet activation. The aim of the present study was to assess the interrelationships between MPV, JAK-2 gene mutation and thromboembolic events in patients with ET and PV. Patients with ET (n = 60) and PV (n = 46) were compared to the secondary erythrocytosis group (n = 19); and a control group of age and sex matched healthy volunteers (n = 52). Besides demogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Important alterations in volume parameters of thrombocytes may have prophylactic and diagnostic importance in thrombotic events and prothrombotic tendency. In addition, increments in the platelet volume causes ischemia and infarction [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Important alterations in volume parameters of thrombocytes may have prophylactic and diagnostic importance in thrombotic events and prothrombotic tendency. In addition, increments in the platelet volume causes ischemia and infarction [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…We identified six previous studies [21,22,[29][30][31][32] assessing role of MPV in Ph-MPN patients (PMF patients comprised a minority of analyzed populations in two works [21,22] and were not included in other studies). These studies investigated relationship between MPV, JAK2 mutational status and history of thrombosis with inconsistent findings among studies.…”
Section: Discussionmentioning
confidence: 99%
“…This makes the IFN and STAT/JAK pathway the potential target to treat atherosclerosis. A few animal studies confirmed therapeutic potentials of IFN blockade resulting in inhibition of atherosclerotic plaque progression, stabilization of lipid- and macrophage-rich advanced plaques in ApoE knockout mice, and reduction of atherosclerosis in the graft vessels and the aorta in mice heart transplantation models [ 88 , 89 , 90 ]. Unfortunately, the inhibition of IFN blockade in atherosclerosis has not been tested in humans yet and studies on IFN inhibition in other indications (Crohn diseases and SLE) have been terminated prematurely due to lack of efficacy [ 87 ].…”
Section: Safety Issues Of Jak Inhibitorsmentioning
confidence: 99%
“…So, the inhibition of this pathway may exert anti-platelet activity [ 88 ]. The opposite conclusions come from the study of Ayer et al, who investigated the role of mutation of JAK2 in the development of thrombosis in chronic myeloproliferative diseases, finding no relationship between thromboembolic events and JAK2 mutation [ 89 ]. Recently, the role of tissue factor (TF) and its regulatory mechanism attracted attention of many researchers.…”
Section: Safety Issues Of Jak Inhibitorsmentioning
confidence: 99%